2020
DOI: 10.1088/1757-899x/849/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety and health construction industry management (OSHCIM): current practice in Malaysia

Abstract: The accident occurred in the construction industry is reportedly the third-highest after manufacturing and agriculture industry. The percentage of accident cases and fatality ratios in the Malaysian construction industry are getting larger and gradually increasing each year. This data indicates that the safety and health performance in the Malaysian construction industry appears to be weak. Henceforth, the Department of Occupational Safety and Health Malaysia (DOSH) through government initiative has introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This guideline serves as a motivator to reduce construction fatality rates by 2020, as well as encourages the adoption of OSHCIM 2017 practices in Malaysia's construction industry. (Mohd et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This guideline serves as a motivator to reduce construction fatality rates by 2020, as well as encourages the adoption of OSHCIM 2017 practices in Malaysia's construction industry. (Mohd et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The construction industry's appalling health and safety record is still a worldwide problem affecting both developed and developing countries where are employment in the construction industry accounts for about 7% of global employment, and more than 100,000 workers are killed at construction sites yearly, accounting for around 35% of the world's occupational fatalities (Boadu et al, 2020;IEA, 2022;Mohd et al, 2020). Researchers have demonstrated that a high percentage of work-related injuries in developed countries are attributed to construction work.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that a high percentage of work-related injuries in developed countries are attributed to construction work. Developed countries like the USA, the UK, the European Union (EU), and Japan still suffer from high fatality rates in the construction sector ranging from 10% to 30% (HSE, 2021;Mohd et al, 2020;Shim et al, 2022). On the other side, the occupational safety condition at construction sites in developing countries is worse compared to those in developed countries.…”
Section: Introductionmentioning
confidence: 99%